2010
DOI: 10.1007/s00267-010-9529-8
|View full text |Cite
|
Sign up to set email alerts
|

A Case History of the Science and Management Collaboration in Understanding Hypoxia Events in Long Bay, South Carolina, USA

Abstract: Communication of knowledge between the scientific and management communities is a difficult process complicated by the distinctive nature of professional career goals of scientists and decision-makers. This article provides a case history highlighting a collaboration between the science and management communities that resulted from a response to a 2004 hypoxia, or low dissolved oxygen, event in Long Bay, off Myrtle Beach, South Carolina. A working group of scientists and decision-makers was established at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Few cases of hypoxia have been observed for shallow coastal ocean environments such as those along the open-ocean, shallow shelf, coastal region off of South Carolina, USA, where hypoxia was first quantitatively observed in 2004 (Sanger et al 2010). At this time, hypoxic conditions were found in the nearshore waters (5 to 7 m depth) off an open beach in the central portion of Long Bay.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Few cases of hypoxia have been observed for shallow coastal ocean environments such as those along the open-ocean, shallow shelf, coastal region off of South Carolina, USA, where hypoxia was first quantitatively observed in 2004 (Sanger et al 2010). At this time, hypoxic conditions were found in the nearshore waters (5 to 7 m depth) off an open beach in the central portion of Long Bay.…”
Section: Introductionmentioning
confidence: 98%
“…That hypoxia occurred just seaward of the surf zone (~0.3 km from the beach-face) was somewhat surprising, given this is an area generally considered to experience high physical mixing. Analysis of limited water quality and meteorological data revealed that the first documented hypoxic event occurred during a period of sustained southwesterly upwelling-favorable winds that coincided with the occurrence of cold bottom water (Sanger et al 2010). Although Long Bay is influenced by coastal upwelling, no evidence existed to suggest that the upwelled water was a direct source of high nutrients or low DO.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water quality surveys conducted during the following week documented hypoxic conditions in the nearshore bottom waters. The unusual flounder behavior was subsequently attributed to these low dissolved oxygen levels (Sanger et al 2010).…”
Section: Introductionmentioning
confidence: 99%